Urate-null rosy mutants of Drosophila melanogaster are hypersensitive to oxygen stress. - Hilliker, A J (1992)
It has been proposed that uric acid is an important scavenger of deleterious oxygen radicals in biological systems [Ames, B. N., Cathcart, R., Schwiers, E. & Hochstein, P. (1981) Proc. Natl. Acad. Sci. USA 78, 6858-6852]. We report here an in vivo investigation of the oxygen defense role of uric acid through an analysis of mutants of the rosy (ry) gene of Drosophila melanogaster. The ry gene is the structural gene for the molybdoenzyme, xanthine dehydrogenase; xanthine dehydrogenase-null ry mutants are therefore unable to synthesize urate. The rationale of our approach was to measure the response of urate-null ry mutants to extraordinary oxygen stress as imposed by exposure to radical-generating agents and as conferred by a genetic defect in superoxide dismutase, an established oxygen defense function. We show that urate-null mutants of the ry locus are hypersensitive to paraquat, ionizing radiation, and hyperoxia. Furthermore, compound mutants doubly deficient for uric acid and Cu/Zn-containing superoxide dismutase are synthetic lethals, which are unable to complete metamorphosis under normal growth conditions. These experiments demonstrate unambiguously the importance of urate in oxygen defense in vivo and support our earlier proposal that the molybdoenzyme genetic system plays a critical role in oxygen defense in Drosophila. They also form the basis for our proposal that metamorphosis in Drosophila imposes a crisis of oxygen stress on the developing imago against which uric acid plays an important organ-specific defense. Finally, the results provide a basis for understanding the syndrome of phenotypes, including the hallmark dull brown eye color, which characterizes mutants of this classic genetic system of Drosophila.